Intellectual knowledge of the individual: notes to Guglielmo de la Mare’s solution - Aiello, Andrea (Acta Philosophica, 2000)
The master of theology William de la Mare is among the first authors of the second half of the 13th century to affirm explicitly the direct understanding of material singulars. However, as opposed to later Franciscan theologians, the author of the "Correctorium fratris Thomae" does not propose original philosophical arguments to pin down a doctrine so widely divergent from the principles of aristotelianism. Is the noetic position of William to be explained simply as a “theological censure”, or is it possible to find some philosophical justification for it? The article presents a re-reading of the problematic noetic affirmation in order to show its coherence with the doctrine of the hylemorphism of the intellectual soul. This doctrine is a metaphysical thesis that the author of the “Correctorium fratris Thomae” and many other post-bonaventurian Franciscan authors regard as necessary.